Borana pastoral system field study report July to September 1983: Water intake and animal production studies - Hughes-Davies, I. (International Livestock Centre for Africa, 1983)
Summarizes findings of a study on relationships between watering frequency, body weight, species, gulp count, water quality and water intake; on effect of water quality on intake; variation of liveweight and heart girth measurements in a 3-day watering regime; and calving histories of cattle kept by Borana pastoralists in Ethiopia.